An analysis on role of judges in interpreting tax legislation - Chanhuwa, Mildred Kudzanai (Rhodes University, Faculty of Commerce, Department of Accounting, 2017)
This thesis focusses on the role of judges as interpreters of tax legislation. It examines the role of judges by analysing how the perceptions of judges can impact on how they interpret legislation. It also analyses various other factors that play a role when judges interpret legislation, in an effort to answer the question to what extent do philosophical theories and interpretative approaches explain the role of judges as interpreters? Jurisprudential theories such as the natural law theory, positivist theories, and American realist theories are used to analyse how judges interpret and how theorists think judges should play their interpretational role. It is noted that in pre-constitutional South Africa the courts followed a positivist paradigm; as a result, the judges used a strict literal approach to interpretation. The new Constitution brought a change in the jurisprudential paradigm accepted in South Africa and has transformed how judges perceive and carry out their role as interpreters of legislation. Judges have now adopted the purposive value-laden approach as authoritative. As custodians of the Constitution, judges should interpret provisions against the values imposed by it. The purposive value-laden interpretational approach allows judges to take into account more considerations and to weigh a provision against the constitutional values. Other issues discussed pertain to how institutional guidelines such as the doctrine of precedent and separation of powers, to a lesser extent, play a role in how judges interpret the law. It is demonstrated that the doctrine of precedent does not limit the role of judges but rather contributes to maintaining certainty, predictability and coherence in the legal system. It is also noted that judicial discretion is the mechanism by which judges use extra-legal factors such as public policy and moral considerations to assist in interpreting legislation.
Keywords: Taxation -- Law and legislation -- South Africa; Law -- South Africa; Judicial discretion -- South Africa; Judicial opinion -- South Africa; Judges -- Attitudes -- South Africa; South Africa. Constitution of the Republic of -- South Africa, 1996